Professionalization of community engagement in flood risk management: Insights from four European countries. (March 2022) - Puzyreva, Kseniia; Henning, Zerline; Schelwald, Renate; Rassman, Hannes; Borgnino, Emanuela; de Beus, Pieke; Casartelli, Sara; Leon, Daniel
Abstract: Flood management has long been dominated by scientific expertise, centralized decision-making, and top-down professional management. However, changing patterns of risk probabilities instigate shifts in the ways floods are managed, bringing forward the necessity for flood mitigation, preparedness and resilience. Community engagement is recognized as paramount in the attainment of these goals. This provokes risk management authorities to facilitate professionalization of community members in becoming risk management stakeholders. Professionalization of community engagement is becoming the esteemed norm, as it ensures better alignment between all stakeholders and increases capacity and efficiency of authority-community collaboration. At the same time, community engagement in flood management in general, and its professionalization, in particular, has its paradoxes. This paper examines the micro-level facets of professionalization of community engagement in Italy, Germany, England, and the Netherlands based on five-months fieldwork conducted in 2020 and discusses the ambivalent implications of professionalization for community engagement in flood risk management. We conclude that professionalization largely contributes to better coordination of the group members' activities, their alignment with risk management needs and priorities, and enhances community members sense of belonging in the professional field of flood risk management. At the same time, professionalization entails the burden of increasing explicit and implicit state requirements for communities. It reinforces participatory limits and reproduces flood risk management unattainability for the broader public.